2007
DOI: 10.1021/je600575r
|View full text |Cite
|
Sign up to set email alerts
|

Solid−Liquid Equilibria under High Pressure of Eight Puren-Alkylcyclohexanes

Abstract: The melting temperature of eight n-alkylcyclohexanes (decylcyclohexane, undecylcyclohexane, dodecylcyclohexane, tridecylcyclohexane, tetradecylcyclohexane, pentadecylcyclohexane, octadecylcyclohexane, and nonadecylcyclohexane) has been measured by means of a high-pressure microscopy device up to 100 MPa. The influence of the alkyl chain length on the melting temperatures and their pressure dependence is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…The difference between both values is 1.7 K, which is higher than experimental uncertainty. On the other hand, no metastable solid phase was detected by Milhet et al [34] for dodecylcyclohexane, although the heating thermograms presented in Fig. 1 show evidence of other transitions that may be associated to polymorphism.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The difference between both values is 1.7 K, which is higher than experimental uncertainty. On the other hand, no metastable solid phase was detected by Milhet et al [34] for dodecylcyclohexane, although the heating thermograms presented in Fig. 1 show evidence of other transitions that may be associated to polymorphism.…”
Section: Resultsmentioning
confidence: 71%
“…Other literature data for the melting point of dodecylcyclohexane show high discrepancies as well: 282.3 K [35], 285 K [36] and 285.8 K (for the triple point) [37]. As Milhet et al [34] point out, dodecylcyclohexane and other naphthenes are difficult to crystallize as they may present high degree of sub-cooling: for dodecylcyclohexane, according to the thermograms presented in Fig. 1, we estimated the difference in temperature of crystallization and melting as approximately 22 K. These kinetic effects may account for the discrepancies found in the value of the melting temperature.…”
Section: Resultsmentioning
confidence: 93%
“…The classical amphiphilic nature of fatty acids is such that they adopt organised supramolecular assemblies in the solid state or on the surface of water supported by hydrogen bonding of the carboxylate head groups and van der Waals interactions of the aliphatic chains, typical of lipid membranes. 25 In the solid state such arrangements can be interdigitated to form a repeat monolayer or the molecules can arrange head to head and form bilayers. On water, the carboxylate head groups associate with the aqueous subphase and chains aggregate into monolayer or bilayer assemblies, a process that can be monitored in a Langmuir trough through pressure area isotherm analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Milhet et al used DSC to observe the melting behavior of n-alkyl cyclohexanes. Their observations revealed that melting temperature increases as chain length increases, but that odd carbon length chains behaved differently from even carbon length chains (Milhet et al, 2007). Adding an extra CH2 to an alkyl chain with an odd number of carbons increased the melting temperature more than if a CH2 was added to an alkyl chain length with an even number of carbons.…”
Section: Monosubstituted Linear Cycloalkanementioning
confidence: 99%